Relationship between' patient's rights charter' and patients' satisfaction in gynecological hospitals. Issue 1 (December 2016) - Farzianpour, Fereshteh; Rahimi Foroushani, Abbas; Shahidi Sadeghi, Niusha; Ansari Nosrati, Saeede
Abstract Background Patient's satisfaction with hospital services is one of the most important indicators of efficiency and quality of services of different hospital wards. Methods This cross-sectional descriptive analytical study was conducted in 2015. The study population included patients in gynecological hospitals of TUMS, and by using questionnaires; data were collected from 304 patients. Statistical analysis was performed using the SPSS 22. Results The rights of patients were mainly observed through "quality of care" (Mean ± SD: 9.65 ± 2.62), "knowing the charges and the right to complain"; (Mean ± SD: 6.00 ± 2.5) "presence of an active system to handle complaints of patients in the hospital and explanation of the error that occurred during service provision to patients by the wrongdoer" is the lowest (7.5 ± 2.62). It was found that patients' satisfaction is below the mean and its different aspects are higher than the mean level. However, the services of physicians and feeding recorded the highest and lowest satisfaction, respectively (19.4 ± 4.25, 20.77 ± 4.39). The mean score of satisfaction of patients admitted with nursing physical care was 24.5 ± 6.2. Conclusion Overall, patients' satisfaction with hospital services was close to the mean. Deficiencies and grievances should be resolved with a correct measure.